THE EFFECT OF ECONOMIC VALUE ADDED (EVA) AND MARKET VALUE ADDED (MVA) ON STOCK RETURN IN PHARMACEUTICAL COMPANIES LISTED ON THE IDX PERIOD 2017-2020 - MEYDA AYU (Indragiri Research Center (ingreat), 2023)
This study aims to determine the effect of Economic Value Added (EVA) and Market Value Added (MVA) on Stock Returns in Pharmaceutical Companies Listed on the IDX for the 2017-2020 period. The population in this study are pharmaceutical companies listed on the IDX in 2017-2020. Sampling using Purposive Sampling method. The samples consisted of 11 companies from 12 pharmaceutical companies listed on the IDX for 2017-2020, so that the research data analyzed consisted of 44 samples. Economic Value Added (EVA) and Market Value Added (MVA) as independent variables and Stock Return as the dependent variable. Data analysis used was SPSS V23. Data collection techniques were carried out by documentation studies, literature studies, and web searching. As for data management techniques using descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. Based on the results of data analysis using the coefficient of determination test (R2) the results of 23.0% Economic Value Added (EVA) and Market Value Added (EVA) jointly affect stock returns, while the remaining 77.0% is influenced by other variables not examined in this study. From the results of the multiple linear regression test, the results of the study obtained the regression equation Y = (-6.646) + (-0.017) X1 + 0,597 X2 + e , based on the results of the t (partial) test shows that partially Economic Value Added (EVA) has no significant effect on Stock Returns with a sig value of 0.935 > 0.05 and Market Value Added (MVA) partially has a significant effect on Stock Returns with a value sig 0.006 <0.05. From the F test (Simultaneous) obtained Fcount 4.489 > Ftable 3.30 with a sig level of 0.020 <0.05 indicating that Economic Value Added (EVA) and Market Value Added (EVA) together have an effect on Stock Returns.